2005
DOI: 10.1189/jlb.0605320
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase localization in the rat neutrophils: immunocytochemical, molecular, and biochemical studies

Abstract: Nitric oxide (NO) modulates diverse functions of polymorphonuclear neutrophils (PMNs), but localization of NO synthase (NOS) and identification of its interacting proteins remain the least defined. The present study discerns subcellular distribution of NOS and caveolin-1, a prominent NOS-interacting protein in rat PMNs. Localization of NOS was explored by confocal and immunogold electron microscopy, and its activity was assessed by L-[3H] arginine and 4,5-diaminofluorescein diacetate (DAF-2DA). Reverse transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 70 publications
(84 reference statements)
7
67
0
3
Order By: Relevance
“…Activation of Src tyrosine kinases is the earliest event that occurs during engagement of ␤2 integrins (2), and these tyrosine kinases have been shown to up-regulate the activity of PLC␥2 (leading to activation of PKC and mobilization of calcium) and PI 3-kinase (leading to the generation of phosphatidylinositol 3,4,5-trisphosphate). Although we don't know yet the link that exists between these signaling molecules and activation of iNOS, it might be that they affect the relocalization of iNOS to a specific compartment (68) and/or its interaction with binding partners. We also found that the effect of NO on the regulation of Rap GTPases is mediated through activation of guanylate cyclase, production of cGMP, and activation of cGKI.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Src tyrosine kinases is the earliest event that occurs during engagement of ␤2 integrins (2), and these tyrosine kinases have been shown to up-regulate the activity of PLC␥2 (leading to activation of PKC and mobilization of calcium) and PI 3-kinase (leading to the generation of phosphatidylinositol 3,4,5-trisphosphate). Although we don't know yet the link that exists between these signaling molecules and activation of iNOS, it might be that they affect the relocalization of iNOS to a specific compartment (68) and/or its interaction with binding partners. We also found that the effect of NO on the regulation of Rap GTPases is mediated through activation of guanylate cyclase, production of cGMP, and activation of cGKI.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, rat neutrophils constitutively express nNOS and generate higher levels of NO; whereas human neutrophils express low level of enzyme at mRNA and protein level. The previous reports from this laboratory have shown the presence of nNOS and iNOS and their subcellular localization but failed to detect eNOS in peripheral rat PMNs (29,30).…”
mentioning
confidence: 95%
“…Control samples were processed similarly as mentioned earlier, omitting the primary antibodies (29).…”
Section: Confocal Microscopymentioning
confidence: 99%
See 2 more Smart Citations